Pathogenicity of a novel bovine adenovirus type 3 with a natural deletion partial fiber gene in BALB/c mice - Li, Qian; He, Shufan; Zou, Yuantong; Yue, Hua; Tang, Cheng; Liu, Jie (Frontiers in Veterinary Science, 2023)
Bovine adenovirus type 3 (BAdV-3) is an important pathogen causing bovine respiratory disease syndrome (BRDC). A novel BAdV-3 with a natural deletion partial fiber gene was isolated in 2020 and named BO/YB24/17/CH. To understand the pathogenicity of this novel BAdV-3 virus, 24 BALB/c mice were inoculated intranasally with BO/YB24/17/CH. All infected mice developed mild clinical signs such as lethargy, weight loss, loss of appetite, and a rough hair coat, and gross lesions were observed as pulmonary punctate hemorrhage, lobular atrophy and splenomegaly. Histopathological examination revealed thickening of alveolar septa, inflammatory cell infiltration, and alveolar epithelial necrosis in lung tissue, and mildly dilated splenic nodules and blurred red-white medullary demarcation in the spleen. Immunohistochemical results further confirmed that the production of the above lesions was due to viral infection. Importantly, unlike previously reported BAdV-3 detection only in the lungs and trachea, this isolate could be detected in multiple organs such as the heart, liver, spleen, kidney, and even blood by virus isolation and titration and real-time PCR methods. Viral titers and viral loads were high throughout the infection period, with a much longer duration of infection than the previously reported HLJ0955 strain. These results suggest that the isolate has a broader tissue tropism and is capable of causing viremia, which may be closely related to the deletion of the fiber shaft domain. This study provides further insight into the pathogenicity of the fiber region deletion strain BO/YB24/17/CH in BALB/c mice, which provides a reference for the prevention and control of BAdV-3 as well as the development of vaccines.